Distribution patterns of the protandric simultaneous hermaphrodite, the spine-shrimp Exhippolysmata oplophoroides (Holthuis, 1948), in the Cananeia-Iguape system on the southern coast of the state of Sao Paulo, Brazil - Bernardi Carvalho, William Gebin [UNESP]; Costa, Rogerio Caetano da [UNESP]; Herrera, Daphine Ramiro [UNESP] (Soc Brasileira Carcinologia, 2020)
The aim of this study was to investigate the spatial and temporal distribution of Exhippolysmata oplophoroides and relate its abundance to various environmental variables (bottom water temperature and salinity, texture of sediment and percentage of dissolved organic matter). The sampling of shrimp and abiotic factors was carried out monthly from July 2012 to June 2014, in seven trawling stations (S1-S7), four of them in the marine area and three in the estuary (southern coast of the state of Sao Paulo, Brazil). The distribution of individuals showed significant differences between stations and between the two years of study (ANOVA, p < 0.05), but not among seasons (p > 0.05). A total of 2005 shrimp were collected, with the highest abundance being found in S4 (n= 937). Bottom salinity and sediment texture were the environmental factors with significant influence on the distribution of the species in the studied region. The low salinity values at S6 and S7, and the low capacity for osmoregulation of E. oplophoroides limit its distribution in the marine environment. High concentrations of silt+clay found at S4 contributed to the accumulation of organic matter, which influenced the high abundance of shrimp there. The information gathered in our study provides valuable results for the knowledge of this species in its area of distribution and contributes to a better understanding of the life history.
Keywords: Abundance; Cananeia; Caridea; ecological distribution; environmental variables